1993
DOI: 10.1093/oxfordjournals.aje.a116592
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exposure to Animals in the Etiology of Campylobacter jejuni/coli Enteritis

Abstract: To determine the role of animals as possible sources for human infection with Campylobacter jejuni/coli, 218 human cases of Campylobacter enteritis diagnosed among members of Group Health Cooperative of Puget Sound, King County, Washington, from April 1982 through September 1983 were compared with 526 controls, randomly selected from Group Health Cooperative members. All subjects were questioned regarding animal exposures one week prior to illness (cases) or interview (controls). There was no increase in risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 0 publications
3
32
1
2
Order By: Relevance
“…Transmission of Campylobacter spp. from dogs and cats to humans has been documented (Wolfs et al, 2001;Damborg et al, 2004), and contact with asymptomatic pets or pets with diarrhea is a recognized risk for contracting campylobacteriosis in humans (Saeed et al, 1993;Tenkate and Stafford, 2001). Exposure to contaminated food, environmental sources, or reverse zoonosis may be a factor predisposing to the presence of antimicrobial-resistant C. jejuni isolates in pets.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission of Campylobacter spp. from dogs and cats to humans has been documented (Wolfs et al, 2001;Damborg et al, 2004), and contact with asymptomatic pets or pets with diarrhea is a recognized risk for contracting campylobacteriosis in humans (Saeed et al, 1993;Tenkate and Stafford, 2001). Exposure to contaminated food, environmental sources, or reverse zoonosis may be a factor predisposing to the presence of antimicrobial-resistant C. jejuni isolates in pets.…”
Section: Discussionmentioning
confidence: 99%
“…A series of case-control studies identified some risk factors for sporadic campylobacteriosis, particularly handling raw poultry (25,26) and eating undercooked poultry (27-31) (Table). Other risk factors accounting for a smaller proportion of sporadic illnesses include drinking untreated water (29); traveling abroad (25); eating barbequed pork (28) or sausage (27); drinking raw milk (29,32) or milk from bird-pecked bottles (33); and contact with dogs (27) and cats (29,31), particularly juvenile pets or pets with diarrhea (25,34). Person-to-person transmission is uncommon (25,32).…”
Section: Transmission To Humansmentioning
confidence: 99%
“…Other reported risk factors for Campylobacter spp. infection included handling of chickens or preparing chickens [47], contact with cats [23], consuming antibiotics before illness [26], eating pork [106], barbequing [57,106], living or working on farms [106], working in slaughterhouses [15], exposure to animals with diarrhea [90], and travel abroad [92]. Traveling to developing countries was associated with Campylobacter with resistance to antimicrobial drugs [38].…”
Section: Exposure and Transmission Of Campylo-bactermentioning
confidence: 99%